THE CONTENT ASPECT OF THE CONCEPTS OF "SEMANTIC FIELD" AND "THEMATIC GROUP" IN THE MODERN RUSSIAN LANGUAGE - Kholmirzaeva Munira Jakhongir kizi (Modern American Journals, 2025)
This article provides a partial overview of the descriptions of the concepts "semantic field" and "thematic group" by Russian linguists. Based on their research, an attempt is made to identify the structural and content features of these concepts.